Micro MPCs and Macro Counterfactuals: The Case of the 2008 Rebates - Jacob D Orchard; Valerie A Ramey; Johannes F Wieland (The Quarterly Journal of Economics, 2025)
ABSTRACT We present evidence that the high estimated marginal propensities to consume (MPCs) from the leading household studies result in implausible macroeconomic counterfactuals. Using the 2008 tax rebate as a case study, we calibrate a standard macro model with the estimated micro MPCs to construct counterfactual macroeconomic consumption paths in the absence of a rebate. The counterfactual paths imply that consumption expenditures would have plummeted in spring and summer 2008 and mostly recovered in September 2008. We use narratives and forecasts to argue that these paths are implausible. We show that standard two-way fixed effect estimates of the micro MPCs are upward biased. When we correct for the biases, we estimate smaller micro MPCs using the CEX data than the previous literature. We show that realistic modifications of the model result in general equilibrium forces that dampen rather than amplify micro MPCs. The combination of smaller micro MPCs and dampening general equilibrium forces implies general equilibrium consumption multipliers that are below 0.2.